ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PRAKTIK PERATAAN LABA (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2007—2010) - Dina Rahmawati; Dul Muid (Diponegoro Journal of Accounting, 2012)
This study aims to analyze the factors that influence income smoothing using a sample of 81 manufacturing companies listed on the Indonesian Stock Exchange within a period of four years beginning in 2007 until 2010 with the selection method of purposive judgment sampling. Eckel index used to classify companies that do or do not practice income smoothing. The variables used in this study is the size of the company, net profit margin, and debt to equity ratio. Statistical analysis used in this study was to statistically test using descriptive statistics and logistic regression models through multivariate testing. The results of classification showed a income smoothing practices by public companies on the Indonesian Stock Exchange. In the multivariate analysis for the three independent variables, only variables of firm size that have a significant effect on the practice of income smoothing. While the net profit margin and debt to equity ratio does not significantly influence the practice of income smoothing.